ANALISIS JENIS PONDASI GEDUNG MESJID AGUNG KOTA TANJUNG BALAI - Irwansyah Irwansyah; Sufrial Hendri (JUITECH: Jurnal Ilmiah Fakultas Teknik Universitas Quality, 2021)
Tanjungbalai City is one of the cities in North Sumatra Province with a population that continues to increase. Tanjungbalai City Government strives to provide services to the community by building a proper and adequate prayer facility in the city of Tanjungbalai. The Grand Mosque accommodates educational activities, a means of interaction, a good place of worship in Tanjungbalai City. Construction of a representative Grand Mosque which becomes the area's "Land Mark" and becomes "City Icon". Then the Planning Activities of the Great Mosque of Tanjungbalai City will be carried out.The construction of the Grand Mosque must pay attention to efficiency, environmental safety, and environmental aesthetics. Environmental security can be achieved by paying attention to the stability of building construction. One of the factors that must be considered in the stability of a mosque is the stability of the foundation. The foundation is a structure that functions to transmit the loads that work on the mosque building to the soil layer below it. In general, the foundation can be divided into shallow foundation and deep foundation. The location of the hard soil layer and the type of soil will affect the selection of the type of foundation, the calculation of the bearing capacity of the foundation, and the settlement that occurs.This study aims to analyze the choice of the right type of foundation to be used by taking into account the stability of the construction. For this reason, it is necessary to analyze the use of the type of foundation in the building of the Tanjungbalai City Grand Mosque.